2021
DOI: 10.1161/atvbaha.121.316397
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine Is Associated With Future Venous Thromboembolism in 2 Prospective Cohorts of Women

Abstract: Objective: Case-control studies have identified plasma homocysteine as a risk marker for venous thromboembolism (VTE). Prospective data, particularly among women, are sparse. We examined whether plasma homocysteine associates with incident VTE in 2 large prospective cohorts of women. Approach and Results: In the WHS (Women’s Health Study), a prospective cohort study of 27 555 women ≥45 years old and free of cardiovascular disease and VTE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…A very large prospective observational study of two populations of women observed a dose-dependent risk association with unprovoked pulmonary embolism and deep vein thrombosis with t-Hcy levels. 54 A significant P-for trend was observed for the mortality risk of patients with coronary artery disease according to HHcy stratified in 4 categories, <9.0, 9.0 -14.9, 15.0 -19.9 and >20.0 µmol/L. 55 A large prospective study conducted in China showed hazard ratios of 1.66 (1.18-2.33) and 4.96 (95%CI 3.03-8.12) for ischemic stroke with moderate and intermediate/major t-Hcy compared to normal t-Hcy, respectively (Figure 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A very large prospective observational study of two populations of women observed a dose-dependent risk association with unprovoked pulmonary embolism and deep vein thrombosis with t-Hcy levels. 54 A significant P-for trend was observed for the mortality risk of patients with coronary artery disease according to HHcy stratified in 4 categories, <9.0, 9.0 -14.9, 15.0 -19.9 and >20.0 µmol/L. 55 A large prospective study conducted in China showed hazard ratios of 1.66 (1.18-2.33) and 4.96 (95%CI 3.03-8.12) for ischemic stroke with moderate and intermediate/major t-Hcy compared to normal t-Hcy, respectively (Figure 2).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although retrospective studies have at times been conflicting, two large cohorts have shown an association between high homocysteine levels and VTE. 12 Other recent research has demonstrated higher than normal levels in symptomatic AIP patients and those receiving haemin or givosiran. 13 Homocysteine is not collected as part of routine thrombophilia screening at Wellington Hospital and although elevated in case 2, the level was only measured following multiple haem infusions and the prescription of givosiran; hence, it is unclear whether the level was raised prior to the development of VTE or the administration of these agents.…”
Section: Discussionmentioning
confidence: 97%
“…Although retrospective studies have at times been conflicting, two large cohorts have shown an association between high homocysteine levels and VTE 12 . Other recent research has demonstrated higher than normal levels in symptomatic AIP patients and those receiving haemin or givosiran 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The most common theory is that MTHFR may provoke a hypercoagulable state by causing homocysteinemia, but research findings regarding this have been inconsistent as well [6]. Some data suggest that homocysteine does in fact cause a prothrombotic state, while other articles suggest that elevated homocysteine only indicates increased cardiovascular risk [4,9] and lowering homocysteine levels does not decrease the risk of venous thrombosis [9]. Furthermore, research that does support hyperhomocysteinemia increasing hypercoagulability has not discovered a precise mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…One possible etiology or risk factor was found to be a previous diagnosis of methylenetetrahydrofolate reductase (MTHFR) polymorphism. Studies have shown that the MTHFR polymorphism can result in reduced activity of methylenetetrahydrofolate reductase resulting in hyperhomocysteinemia [3], and elevated homocysteine may result in a prothrombotic state or serve as a marker for cardiovascular risk [4]. Several studies have hypothesized different mechanisms for the potential prothrombotic state that can result from hyperhomocysteinemia [5].…”
Section: Introductionmentioning
confidence: 99%